2008
DOI: 10.1080/00365540802179691
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies investigation in Pneumocystis jirovecii carriers

Abstract: It is well documented that antiphospholipid antibodies are increased in patients with HIV-1 infection and these are most commonly seen in those with Pneumocystis jirovecii pneumonia. Therefore it has been proposed that this could be the cause of its presence. Recently, P. jirovecii subclinical infection has been described in non-immunodeficient patients. We report here our experience concerning the possible relationship between P. jirovecii infection in non-immunocompromized adults and the production of antiph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The reported prevalence of lupus anticoagulant in HIV-infected patients is generally low, but prevalences up to 72% were documented. [27][28][29] Majluf-Cruz et al 6 observed in- No other studies on APCsr in HIV-infected patients have been described so far. APCsr and increased risk of vascular complications have been found in patients with systemic lupus erythematosus and primary cytomegalovirus infection.…”
Section: Discussionmentioning
confidence: 97%
“…The reported prevalence of lupus anticoagulant in HIV-infected patients is generally low, but prevalences up to 72% were documented. [27][28][29] Majluf-Cruz et al 6 observed in- No other studies on APCsr in HIV-infected patients have been described so far. APCsr and increased risk of vascular complications have been found in patients with systemic lupus erythematosus and primary cytomegalovirus infection.…”
Section: Discussionmentioning
confidence: 97%